TiO2 / Cu-Yb MOF composite photocatalyst as well as preparation method and application thereof
By uniformly covering TiO2 nanoparticles on the surface of Cu-Yb MOF nanosheets, the problems of poor light absorption capacity and poor electron-hole separation capacity of traditional photocatalysts are solved, and efficient photocatalytic hydrogen production effect is achieved.
Patent Information
- Application Number
- CN202411618606.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-13
AI Technical Summary
Traditional photocatalysts have problems such as poor light absorption capacity, low chemical stability and poor electron-hole separation capacity, resulting in low photocatalytic activity.
TiO2/Cu-Yb MOF composite photocatalyst is used to uniformly cover TiO2 nanoparticles on the surface of Cu-Yb MOF nanosheets, and the oxygen coordination characteristics and in-situ growth method of ytterbium ions are used to improve the distribution uniformity and photodynamic activity of TiO2.
The efficiency and cycle stability of photocatalytic hydrogen production are significantly improved, and the hydrogen production efficiency reaches 5424 μmol/g/h, and the chemical stability of the photocatalyst is improved.
Smart Images

Figure CN119680645A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic hydrogen production, and in particular to a TiO 2 / Cu-Yb MOF composite photocatalyst and its preparation method and application. Background Art
[0002] Solar energy has the advantages of being environmentally friendly, cheap and easily available, and has become a recognized renewable energy source with broad application prospects. At present, it is generally believed that using solar energy to decompose water into hydrogen is one of the effective ways to solve the energy crisis.
[0003] In 1972, Fujishima et al. proved through experiments that titanium dioxide (TiO 2 ) Semiconductors can be used as photocatalysts to decompose water to produce hydrogen, and this research has aroused great interest among researchers. Since then, the hydrogen evolution technology using semiconductors as photocatalysts has received widespread attention, and many materials including metal oxides, metal organic frameworks (MOFs) and carbon nitride have been applied to photocatalysis. However, traditional photocatalysts face problems such as poor light absorption, low chemical stability, and especially poor electron-hole separation ability, which has led to the demand for a new generation of photocatalysts.
[0004] Patent publication number CN109482241A discloses a TiO 2 / MOF-5 photocatalyst and preparation method thereof, the TiO 2 The preparation method of MOF-5 photocatalyst comprises the following steps: providing MOF-5 material; preparing a mixed solution of ethanol and water, and adjusting the pH value to 2-4 to obtain a first solution; mixing tetrabutyl titanate, glacial acetic acid and ethanol to form a second solution; adding the MOF-5 material to the second solution to obtain a third solution; adding the first solution to the third solution and stirring evenly; filtering, aging the obtained filtrate, drying, and calcining to obtain TiO 2 / MOF-5 photocatalyst. However, in this method, TiO 2 / MOF-5 photocatalyst is easily affected by local TiO 2 Too high a concentration will cause agglomeration, making TiO 2 The distribution is uneven and the photocatalytic activity is low. Summary of the invention
[0005] The purpose of the present invention is to provide a TiO 2 / Cu-YbMOF composite photocatalyst and its preparation method and application, the prepared TiO 2 / Cu-Yb MOF composite photocatalyst has higher photodynamic activity and photocatalytic activity, which can effectively solve the problem of easy recombination of electrons and holes.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a TiO 2 The preparation method of the Cu-Yb MOF composite photocatalyst comprises the following steps:
[0008] S1, introducing copper salt and ytterbium salt into tetrakis(4-carboxyphenyl)porphine (TCPP) in sequence by heating reaction to obtain Cu-Yb MOF powder;
[0009] S2, preparing Cu-Yb MOF powder into Cu-Yb MOF dispersion, adding heat-treated tetrabutyl titanate ethanol solution into the Cu-Yb MOF dispersion, stirring and heating, cooling, washing, and centrifuging to obtain an intermediate;
[0010] S3, preparing the intermediate into an intermediate dispersion, and performing solvent thermal compounding to obtain TiO 2 / Cu-Yb MOF photocatalyst, the reaction is completed.
[0011] Further, in step S1, the preparation process of the Cu-Yb MOF powder is specifically as follows: dissolving TCPP in an organic solvent, heating to 100-150°C, stirring and heating, adding an organic solvent containing a copper salt, condensing and refluxing at 100-150°C, adding an organic solvent containing an ytterbium salt, continuing to condense and reflux at 110-160°C, cooling to room temperature, washing, centrifuging, and drying to obtain Cu-Yb MOF. Ytterbium metal ions are metal nodes to form a MOF network structure.
[0012] Furthermore, the mass ratio of the copper salt, ytterbium salt and TCPP is 6 to 10:6 to 10:3;
[0013] The mass volume ratio of the copper salt to the organic solvent is 7.5 to 12.5 mg / ml;
[0014] The copper salt is copper chloride (CuCl 2 );
[0015] The ytterbium salt is ytterbium nitrate (Yb(NO 3 ) 3 );
[0016] The organic solvent is N,N-dimethylformamide (DMF).
[0017] Furthermore, TCPP is ultrasonically dissolved in an organic solvent, the temperature is raised to 100-150° C., stirred and heated, an organic solvent containing a copper salt is added dropwise, and condensation reflux is maintained at 100-150° C. for 10-60 min, and then an organic solvent containing an ytterbium salt is added dropwise, and condensation reflux is continued at 110-160° C. for 4-10 h, cooled to room temperature, washed with ethanol 1-5 times, centrifuged at 5500-6500 rpm for 2-10 min, and dried at 40-80° C. for 1-5 h to obtain Cu-Yb MOF.
[0018] Furthermore, in step S2, the mass volume ratio of Cu-Yb MOF to tetrabutyl titanate in the Cu-Yb MOF dispersion is 4:25-100 mg / μL. The amount of tetrabutyl titanate added was changed to explore the effect of Cu-Yb MOF loading TiO 2 to achieve the best hydrogen production efficiency and hydrogen production cycle stability.
[0019] Further, in step S2, the mass volume ratio of Cu-Yb MOF and the dispersion medium in the Cu-Yb MOF dispersion is 0.5 to 0.8 mg / mL;
[0020] The volume ratio of tetrabutyl titanate to ethanol in the tetrabutyl titanate ethanol solution is (2.5-10)×10 -3 :1.
[0021] Furthermore, the dispersion medium in the Cu-Yb MOF dispersion includes water and ethanol, and the volume ratio of water to ethanol is (1-5):1, preferably 2:1.
[0022] Furthermore, in step S2, the temperature of the heat treatment of the ethanol solution of tetrabutyl titanate is 80-90° C., and the time is 1-2 hours; the temperature of the stirring heating is 80-90° C., and the time is 4-6 hours.
[0023] Further, in step S3, the dispersion medium in the intermediate dispersion liquid includes water and DMF in a volume ratio of 30 to 40:1;
[0024] The mass volume ratio of the intermediate and the dispersion medium is 2.3-6.9 mg / ml.
[0025] Furthermore, in step S3, the temperature of the solvent thermal compound is 100-150° C., the time is 10-15 hours, and the solvent thermal compound is carried out in a reaction vessel.
[0026] The second technical solution of the present invention is to provide a TiO 2 / Cu-Yb MOF composite photocatalyst, which is prepared by the above-mentioned preparation method.
[0027] Furthermore, TiO 2 In the TiO / Cu-Yb MOF composite photocatalyst, 2 The nanoparticles are evenly covered on the surface of Cu-YbMOF nanosheets, with almost no TiO 2 Irregular aggregation of particles.
[0028] The third technical solution of the present invention is to provide a TiO 2 / Cu-Yb MOF composite photocatalyst in the field of photocatalysis, the TiO 2 / Cu-Yb MOF composite photocatalyst as photocatalyst for hydrogen production by water splitting.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] (1) The present invention utilizes the characteristic that ytterbium ions are easy to coordinate with oxygen. First, copper and ytterbium metal ions are introduced into TCPP by heating to form a Cu-Yb MOF network structure. Then, TiO 2 Nanoparticles are uniformly loaded on the surface of Cu-Yb MOF nanosheets. Compared with TiO 2 and Cu-Yb MOF, TiO 2 / Cu-Yb MOF composite photocatalyst 2 The generated electrons are transferred to MOF in a timely manner, thereby separating the electrons and holes, solving the problem of easy recombination of electrons and holes, and further improving the performance of photocatalytic hydrogen production.
[0031] (2) Even if tetrabutyl titanate is directly added to the MOF aqueous solution under stirring and hydrolyzed (in situ growth method), the TiO generated by local hydrolysis will still 2 The concentration is too high and agglomeration is inevitable. After the introduction of ytterbium ions, due to the interaction between ytterbium ions and TiO 2 The strong interaction between oxygen and TiO 2 Combined with the oxygen in MOF, TiO 2 The distribution is dense and uniform, so TiO 2 The contact interface with MOF is larger and there are more active sites. At the same time, the in-situ growth method and oven heating composite method greatly enhance the TiO 2 The interaction with MOF leads to improved chemical stability of the composites synthesized by this method.
[0032] (3) In the present invention, TCPP is a monomer for MOF synthesis, and ytterbium ions are evenly distributed in the synthesized MOF nanosheets. At the same time, due to the effective energy and electron transfer between TCPP and ytterbium ions, the constructed 2D Yb-MOF nanosheets have higher photodynamic activity than other synthesized 2D MOFs, and the photocatalytic activity is greatly improved on the basis of improving the absorption of light.
[0033] (4) The present invention adjusts the amount of tetrabutyl titanate added to adjust the TiO 2 The loading ratio is adjusted to explore the optimal composite material with the best hydrogen production efficiency and hydrogen production cycle stability. 2 / Cu-Yb MOF composite photocatalyst has an efficiency of hydrogen production of 5424 μmol / g / h.
[0034] (5) MOF materials are often used to design materials with filtration and adsorption functions due to their huge specific surface area and rich pore structure. 2 / Cu-Yb MOF composite materials not only have the advantages of traditional MOF materials, but also have excellent photoelectrochemical properties. They can be used in the field of photocatalytic hydrogen production, which has high novelty and broad application prospects. The present invention provides a new method and approach for exploring the application of MOF materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The TiO 2 / SEM image of Cu-Yb MOF photocatalyst powder;
[0036] Figure 2 The TiO 2 / Cu-Yb MOF photocatalyst and the TiO 2 / Cu-Zn MOF、TiO 2 @Comparison of the hydrogen production performance of Cu-Yb MOF and Cu-Yb MOF by photocatalytic water splitting, (a) Examples 1 to 4, (b) Example 1 and Comparative Examples 1 to 3;
[0037] Figure 3 The TiO 2 / Cu-Yb MOF photocatalyst and the TiO 2 / Cu-Zn MOF、TiO 2 @Transient photocurrent response diagram of Cu-Yb MOF and Cu-Yb MOF, (a) Examples 1 to 4, (b) Example 1 and Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0039] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.
[0040] All the following chemicals were used as received without further purification. TCPP has a CAS number of 14609-54-2, a brand of Frontier Scientific, purchased from Anolon (Beijing) Biotechnology Co., Ltd.; DMF has a CAS number of 68-12-2, a brand of Adamas, purchased from Shanghai Titan Technology Co., Ltd.; tetrabutyl titanate has a CAS number of 5593-70-4, a brand of Greagent, purchased from Shanghai Titan Technology Co., Ltd.; TiO 2 The CAS number is 13463-67-7, 20nm (P25), the brand is Roen, and it was purchased from Shanghai Yien Chemical Technology Co., Ltd.
[0041] Example 1
[0042] A TiO 2 / Cu-Yb MOF composite photocatalyst, the preparation method thereof is as follows:
[0043] (I) Synthesis of Cu-Yb MOF
[0044] 30 mg TCPP was added to 2 ml DMF and dissolved by ultrasonication. Then, the mixture was transferred to a 10 ml round-bottom flask in an oil bath and heated to 120 °C with stirring. 70 mg CuCl was added dropwise. 2 2 ml of DMF solution was maintained at 120 °C for 20 min. Then 70 mg of Yb(NO 3 ) 3 4 ml of DMF solution was added and kept at 120°C for 5 h10 min. Then, it was cooled to room temperature and washed with ethanol for 3 times. After centrifugation at 6500 rpm for 5 min, it was dried at 60°C in vacuum for 3 h to obtain Cu-Yb MOF powder.
[0045] (II) In situ growth of TiO on the Cu-Yb MOF surface 2 Nanoparticles
[0046] 150μl of tetrabutyl titanate was dropped into 20ml of ethanol, transferred to the oil bath in 50ml three-necked flask A, heated to 85℃ and stirred for 1h. During this period, 8ml of deionized water and 4ml of anhydrous ethanol were measured and mixed, and 8mg of Cu-YbMOF powder synthesized in the first step was added, and the powder was evenly dispersed by ultrasound for 30min. Then the dispersion was transferred to 50ml three-necked flask B. Then the solution in Mitsui flask A was added dropwise to three-necked flask B while hot. Keep heating and stirring at 85℃ for 4h. Then naturally cooled to room temperature and washed with ethanol twice, and centrifuged at 6000rpm for 5min to obtain the intermediate. 43.5mg of the intermediate was added to 8ml of deionized water and 250μl of DMF, and then oscillated and mixed to obtain an intermediate dispersion, which was transferred to a 10ml reactor and heated to 120℃ in an oven for 12h of solvent thermal composite reaction. After cooling to room temperature naturally, the mixture was washed with ethanol three times, centrifuged at 5500 rpm for 5 min, and vacuum dried at 60 °C for 3 h to obtain TiO 2 / Cu-Yb MOF photocatalyst powder.
[0047] (III) Photocatalytic hydrogen production conditions
[0048] Take 10 mg TiO 2 / Cu-Yb MOF photocatalyst powder was ultrasonicated in 10ml deionized water for 10min, then transferred to the photocatalytic reactor, and 40ml deionized water was added while stirring. Methanol and triethanolamine were mixed as sacrificial reagents, with methanol: triethanolamine = 7:1. 10ml of the mixed sacrificial reagent was added to the photocatalytic reactor. After nitrogen was passed for 10min, it was placed under a mercury lamp for irradiation, and the hydrogen content was measured once an hour for a total of 6h.
[0049] Example 2
[0050] A TiO 2 / Cu-Yb MOF composite photocatalyst, the preparation method thereof is as follows:
[0051] (I) Synthesis of Cu-Yb MOF
[0052] 30 mg of TCPP was added to 2 ml of DMF and dissolved by ultrasonication. Then, the mixture was transferred to a 10 ml round-bottom flask in an oil bath and heated to 100 °C with stirring. Then, 60 mg of CuCl was added dropwise. 2 2 ml of DMF solution was maintained at 100 °C for 30 min. Then 60 mg of Yb(NO 3 ) 3 4 ml of DMF solution was added and kept at 110°C for 6 h of condensation reflux. Then it was naturally cooled to room temperature and washed with ethanol for 3 times. After centrifugation at 6000 rpm for 5 min, it was vacuum dried at 60°C for 3 h to obtain Cu-Yb MOF powder.
[0053] (II) In situ growth of TiO on the Cu-Yb MOF surface 2 Nanoparticles
[0054] 100μl of tetrabutyl titanate was dropped into 20ml of ethanol, transferred to the oil bath in 50ml three-necked flask A, heated to 80℃ and stirred for 1h. During this period, 6.6ml of deionized water and 3.4ml of anhydrous ethanol were measured and mixed, and 8mg of Cu-Yb MOF powder synthesized in the first step was added, and the powder was evenly dispersed by ultrasound for 30min. Then the dispersion was transferred to 50ml three-necked flask B. Then the solution in Mitsui flask A was added dropwise to three-necked flask B while hot. Keep heating and stirring at 80℃ for 6h. Then naturally cooled to room temperature and washed with ethanol twice, and centrifuged at 6000rpm for 5min to obtain the intermediate. 31.7mg of the intermediate was added to 8ml of deionized water and 200μl of DMF, and then shaken and mixed to obtain the intermediate dispersion, which was transferred to a 10ml reactor and heated to 100℃ in an oven, and the solvent thermal composite reaction was 12h. After cooling to room temperature naturally, the mixture was washed with ethanol three times, centrifuged at 6000 rpm for 5 min, and vacuum dried at 60 °C for 3 h to obtain TiO 2 / Cu-Yb MOF photocatalyst powder.
[0055] (III) Photocatalytic hydrogen production conditions
[0056] Take 10 mg TiO 2 / Cu-Yb MOF photocatalyst powder was ultrasonicated in 10ml deionized water for 10min, then transferred to the photocatalytic reactor, and 40ml deionized water was added while stirring. Methanol and triethanolamine were mixed as sacrificial reagents, with methanol: triethanolamine = 7:1. 10ml of the mixed sacrificial reagent was added to the photocatalytic reactor. After nitrogen was passed for 10min, it was placed under a mercury lamp for irradiation, and the hydrogen content was measured once an hour for a total of 6h.
[0057] Example 3
[0058] A TiO 2 / Cu-Yb MOF composite photocatalyst, the preparation method thereof is as follows:
[0059] (I) Synthesis of Cu-Yb MOF
[0060] 30 mg of TCPP was added to 2 ml of DMF and dissolved by ultrasonication. Then, the mixture was transferred to a 10 ml round-bottom flask in an oil bath and heated to 150 °C with stirring. Then, 100 mg of CuCl was added dropwise. 2 2 ml of DMF solution was maintained at 150 °C for 25 min. Then 100 mg of Yb(NO 3 )3 4 ml of DMF solution was added and kept at 160°C for 5 h30 min. Then, it was cooled to room temperature and washed with ethanol for 3 times. After centrifugation at 6500 rpm for 5 min, it was dried at 60°C for 3 h to obtain Cu-Yb MOF powder.
[0061] (II) In situ growth of TiO on the Cu-Yb MOF surface 2 Nanoparticles
[0062] 50μl of tetrabutyl titanate was dropped into 20ml of ethanol, transferred to the oil bath in 50ml three-necked flask A, heated to 90℃ and stirred for 1h. During this period, 10.7ml of deionized water and 5.3ml of anhydrous ethanol were measured and mixed, and 8mg of Cu-YbMOF powder synthesized in the first step was added, and the powder was evenly dispersed by ultrasound for 30min. Then the dispersion was transferred to 50ml three-necked flask B. Then the solution in Mitsui flask A was added dropwise to three-necked flask B while hot. Keep heating and stirring at 90℃ for 5h. Then naturally cooled to room temperature and washed with ethanol twice, and centrifuged at 6000rpm for 5min to obtain the intermediate. 19.8mg of the intermediate was added to 8ml of deionized water and 267μl of DMF, and then oscillated and mixed to obtain an intermediate dispersion, which was transferred to a 10ml reactor and heated to 150℃ in an oven for 12h of solvent thermal composite reaction. After cooling to room temperature naturally, the mixture was washed with ethanol three times, centrifuged at 6500 rpm for 5 min, and vacuum dried at 60 °C for 3 h to obtain TiO 2 / Cu-Yb MOF photocatalyst powder.
[0063] (III) Photocatalytic hydrogen production conditions
[0064] Take 10 mg TiO 2 / Cu-Yb MOF photocatalyst powder was ultrasonicated in 10ml deionized water for 10min, then transferred to the photocatalytic reactor, and 40ml deionized water was added while stirring. Methanol and triethanolamine were mixed as sacrificial reagents, with methanol: triethanolamine = 7:1. 10ml of the mixed sacrificial reagent was added to the photocatalytic reactor. After nitrogen was passed for 10min, it was placed under a mercury lamp for irradiation, and the hydrogen content was measured once an hour for a total of 6h.
[0065] Example 4
[0066] A TiO 2 / Cu-Yb MOF composite photocatalyst, the preparation method thereof is as follows:
[0067] (I) Synthesis of Cu-Yb MOF
[0068] 30 mg TCPP was added to 2 ml DMF and dissolved by ultrasonication. Then, the mixture was transferred to a 10 ml round-bottom flask in an oil bath and heated to 120 °C with stirring. 70 mg CuCl was added dropwise. 2 2 ml of DMF solution was maintained at 120 °C for 20 min. Then 70 mg of Yb(NO 3 ) 3 4 ml of DMF solution was added and kept at 120°C for 5 h10 min. Then, it was cooled to room temperature and washed with ethanol for 3 times. After centrifugation at 6500 rpm for 5 min, it was dried at 60°C in vacuum for 3 h to obtain Cu-Yb MOF powder.
[0069] (II) In situ growth of TiO on the Cu-Yb MOF surface 2 Nanoparticles
[0070] 200μl of tetrabutyl titanate was dropped into 20ml of ethanol, transferred to the oil bath in 50ml three-necked flask A, heated to 85℃ and stirred for 1h. During this period, 8ml of deionized water and 4ml of anhydrous ethanol were measured and mixed, and 8mg of Cu-YbMOF powder synthesized in the first step was added, and the powder was evenly dispersed by ultrasound for 30min. Then the dispersion was transferred to 50ml three-necked flask B. Then the solution in Mitsui flask A was added dropwise to three-necked flask B while hot. Keep heating and stirring at 85℃ for 4h. Then naturally cooled to room temperature and washed with ethanol twice, and centrifuged at 6000rpm for 5min to obtain the intermediate. 55.3mg of the intermediate was added to 8ml of deionized water and 250μl of DMF, and then oscillated and mixed to obtain an intermediate dispersion, which was transferred to a 10ml reactor and heated to 120℃ in an oven for 12h of solvent thermal composite reaction. After cooling to room temperature naturally, the mixture was washed with ethanol three times, centrifuged at 5500 rpm for 5 min, and vacuum dried at 60 °C for 3 h to obtain TiO 2 / Cu-Yb MOF photocatalyst powder.
[0071] (III) Photocatalytic hydrogen production conditions
[0072] Take 10 mg TiO 2 / Cu-Yb MOF photocatalyst powder was ultrasonicated in 10ml deionized water for 10min, then transferred to the photocatalytic reactor, and 40ml deionized water was added while stirring. Methanol and triethanolamine were mixed as sacrificial reagents, with methanol: triethanolamine = 7:1. 10ml of the mixed sacrificial reagent was added to the photocatalytic reactor. After nitrogen was passed for 10min, it was placed under a mercury lamp for irradiation, and the hydrogen content was measured once an hour for a total of 6h.
[0073] Comparative Example 1
[0074] A TiO 2 / Cu-Zn MOF composite photocatalyst, compared with Example 1, the other conditions remain unchanged except that Yb(NO 3 ) 3 Replaced by Zn(NO 3 ) 2 .
[0075] The preparation method comprises the following steps:
[0076] (I) Synthesis of Cu-Zn MOF
[0077] 30 mg TCPP was added to 2 ml DMF and dissolved by ultrasonication. Then, the mixture was transferred to a 10 ml round-bottom flask in an oil bath and heated to 120 °C with stirring. 70 mg CuCl was added dropwise. 2 2 ml of DMF solution was maintained at 120 °C for 20 min. Then 70 mg of Zn(NO 3 ) 2 4 ml of DMF solution was added and refluxed at 120°C for 5 h10 min. Then, the mixture was cooled to room temperature and washed with ethanol for 3 times. The mixture was centrifuged at 5500 rpm for 5 min and dried under vacuum at 60°C for 3 h to obtain Cu-Zn MOF powder.
[0078] (ii) In situ growth of TiO on the Cu-Zn MOF surface 2 Nanoparticles
[0079] 150μl of tetrabutyl titanate was dropped into 20ml of ethanol, transferred to the oil bath in 50ml three-necked flask A, heated to 85℃ and stirred for 1h. During this period, 8ml of deionized water and 4ml of anhydrous ethanol were measured and mixed, and 8mg of Cu-ZnMOF powder synthesized in the first step was added, and the powder was evenly dispersed by ultrasound for 30min. The dispersion was then transferred to 50ml three-necked flask B. The solution in Mitsui flask A was then added dropwise to three-necked flask B while hot. Keep heating and stirring at 85℃ for 4h. Then naturally cooled to room temperature and washed with ethanol twice, and centrifuged at 6000rpm for 5min to obtain the intermediate. 43.5mg of the intermediate was added to 8ml of deionized water and 250μl of DMF, and then shaken and mixed to obtain an intermediate dispersion, which was transferred to a 10ml reactor and heated to 120℃ in an oven for 12h of solvent thermal composite reaction. After cooling to room temperature naturally, the mixture was washed with ethanol three times, centrifuged at 6000 rpm for 5 min, and vacuum dried at 60 °C for 3 h to obtain TiO 2 / Cu-Zn MOF photocatalyst powder.
[0080] (III) Photocatalytic hydrogen production conditions
[0081] Take 10 mg TiO 2 / Cu-Zn MOF photocatalyst powder was ultrasonicated in 10ml deionized water for 10min, then transferred to the photocatalytic reactor, and 40ml deionized water was added while stirring. Methanol and triethanolamine were mixed as sacrificial reagents, with methanol: triethanolamine = 7:1. 10ml of the mixed sacrificial reagent was added to the photocatalytic reactor. After nitrogen was passed for 10min, it was placed under a mercury lamp for irradiation, and the hydrogen content was measured once an hour for a total of 6h.
[0082] Comparative Example 2
[0083] A TiO 2 @Cu-Yb MOF composite photocatalyst, compared with Example 1, the other conditions remain unchanged, but the in-situ growth method is not used, TiO 2 The source is commercially available TiO 2 , model P25, rather than produced by hydrolysis of tetrabutyl titanate.
[0084] (I) Synthesis of Cu-Yb MOF
[0085] 30 mg TCPP was added to 2 ml DMF and dissolved by ultrasonication. Then, the mixture was transferred to a 10 ml round-bottom flask in an oil bath and heated to 120 °C with stirring. 70 mg CuCl was added dropwise. 2 2 ml of DMF solution was maintained at 120 °C for 20 min. Then 70 mg of Yb(NO 3 ) 3 4 ml of DMF solution was added and refluxed at 120°C for 5 h10 min. Then, the mixture was cooled to room temperature and washed with ethanol for 3 times. The mixture was centrifuged at 5500 rpm for 5 min and dried under vacuum at 60°C for 3 h to obtain Cu-Yb MOF powder.
[0086] (II) In situ growth of TiO on the Cu-Yb MOF surface 2 Nanoparticles
[0087] 35.5 mg TiO 2After grinding, add 20ml of ethanol, transfer to the oil bath in 50ml three-necked flask A, heat to 85℃ and stir for 1h. During this period, measure 8ml of deionized water and 4ml of anhydrous ethanol, mix and add 8mg of Cu-YbMOF powder synthesized in the first step, and ultrasonicate for 30min to disperse the powder evenly. Then transfer this dispersion to 50ml three-necked flask B. Then add the dispersion in Mitsui flask A dropwise to three-necked flask B while hot. Keep heating and stirring at 85℃ for 4h. Then cool naturally to room temperature and wash with ethanol twice, centrifuge at 6000rpm for 5min to obtain the intermediate. Add 43.5mg of the intermediate to 8ml of deionized water and 250μl of DMF, shake and mix evenly to obtain the intermediate dispersion, transfer to a 10ml reactor, heat to 120℃ in an oven, and solvent thermally react for 12h. Cool naturally to room temperature and wash with ethanol 3 times, centrifuge at 6000rpm for 5min, and vacuum dry at 60℃ for 3h to obtain TiO 2 @Cu-Yb MOF photocatalyst powder.
[0088] (III) Photocatalytic hydrogen production conditions
[0089] Take 10 mg TiO 2 @Cu-Yb MOF photocatalyst powder was ultrasonicated in 10ml deionized water for 10min, then transferred to the photocatalytic reactor, and 40ml deionized water was added while stirring. Methanol and triethanolamine were mixed as sacrificial reagents, with methanol: triethanolamine = 7:1. 10ml of the mixed sacrificial reagent was added to the photocatalytic reactor. After nitrogen was passed for 10min, it was placed under a mercury lamp for irradiation, and the hydrogen content was measured once an hour for a total of 6h.
[0090] Comparative Example 3
[0091] A Cu-Yb MOF photocatalyst, compared with Example 1, the other conditions remain unchanged, and the second step of in-situ growth of TiO on the surface of Cu-YbMOF is removed. 2 Nanoparticles.
[0092] (I) Synthesis of Cu-Yb MOF
[0093] 30 mg TCPP was added to 2 ml DMF and dissolved by ultrasonication. Then, the mixture was transferred to a 10 ml round-bottom flask in an oil bath and heated to 120 °C with stirring. 70 mg CuCl was added dropwise. 2 2 ml of DMF solution was maintained at 120 °C for 20 min. Then 70 mg of Yb(NO 3 ) 34 ml of DMF solution was added and refluxed at 120°C for 5 h10 min. Then, the mixture was cooled to room temperature and washed with ethanol for 3 times. The mixture was centrifuged at 5500 rpm for 5 min and dried under vacuum at 60°C for 3 h to obtain Cu-Yb MOF powder.
[0094] (II) Photocatalytic hydrogen production conditions
[0095] Take 10mg of Cu-Yb MOF photocatalyst powder and ultrasonicate it in 10ml of deionized water for 10min, then transfer it to the photocatalytic reactor and add 40ml of deionized water while stirring. Prepare a mixed sacrificial reagent of methanol and triethanolamine, methanol: triethanolamine = 7:1. Take 10ml of the mixed sacrificial reagent and add it to the photocatalytic reactor. After passing nitrogen for 10min, place it under a mercury lamp and measure the hydrogen content once every hour for a total of 6h.
[0096] The present invention takes the products prepared in Examples 1 to 4 and Comparative Examples 1 to 3 as examples to analyze the results:
[0097] The TiO prepared in Example 1 of the present invention 2 / Cu-Yb MOF morphology and structure Figure 1 Shown: TiO 2 The nanoparticles are evenly and densely covered on the surface of Cu-Yb MOF nanosheets, with almost no irregular agglomeration. This is the result of the combined effect of the introduction of ytterbium ions and the in-situ growth method.
[0098] TiO prepared in Examples 1 to 4 of the present invention 2 / Cu-Yb MOF hydrogen production activity Figure 2 (a) shows: the 6h hydrogen production of Example 1 is 32.5mmolg -1 , for Example 2 (27.9mmolg -1 ) is 1.16 times that of Example 3 (18.8mmolg -1 ) is 1.7 times that of Example 4 (24.8mmolg -1 ) is 1.3 times. Among them, TiO 2 The loading ratios of TiO in Examples 1 to 4 are 81.6%, 74.8%, 59.8% and 85.6% respectively. 2 The composites with different loading ratios all showed good photocatalytic performance, which further indicated that the ratio performance of Example 1 was the best.
[0099] Among them, TiO 2 The calculation method of the load ratio is:
[0100]
[0101] Among them, M 钛酸四丁酯 =340,
[0102] The TiO prepared in Example 1 of the present invention 2 / Cu-Yb MOF, TiO prepared in Comparative Example 1 2 / Cu-Zn MOF, TiO prepared in Comparative Example 2 2 @Cu-Yb MOF and Cu-Yb MOF prepared in Comparative Example 3 are as follows Figure 2 (b) shows that the amount of hydrogen produced in Comparative Example 1 (ytterbium ions replaced by zinc ions) is only 19 mmolg -1 ; Comparative Example 2 (in situ growth method replaced by classical method) is even less, only 18.1mmolg -1 ; Comparative Example 3 (no TiO loading 2 ) is the minimum, and the hydrogen production is 0.6mmolg -1 The hydrogen production of comparative example 3 is the lowest, which proves that the loaded TiO 2 Meanwhile, the hydrogen production of Comparative Examples 1 and 2 is less than 60% of that of Example 1, indicating that the photocatalytic activity will be greatly reduced if ytterbium ions are not introduced or the in-situ growth method is not adopted.
[0103] TiO prepared in Examples 1 to 4 of the present invention 2 / Cu-Yb MOF transient photocurrent response Figure 3 As shown in (a), the TiO prepared in Example 1 of the present invention 2 / Cu-Yb MOF, TiO prepared in Comparative Example 1 2 / Cu-Zn MOF, TiO prepared in Comparative Example 2 2 @Cu-Yb MOF and Cu-Yb MOF prepared in Comparative Example 3 are as follows Figure 3 (b) as shown: Figure 2 The results of photocatalytic hydrogen production are corresponding. The higher the transient photocurrent, the higher the efficiency of electron-hole separation and transfer of the composite material, and the higher the photocatalytic hydrogen production activity. This further confirms that the high photocatalytic performance of the material is due to its excellent photoelectrochemical properties, rather than accidental factors, thus ensuring the repeatability of its application.
[0104] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a TiO2 / Cu-Yb MOF composite photocatalyst, characterized in that: The following steps are involved: S1, introducing copper salt and ytterbium salt into TCPP in sequence by heating reaction to obtain Cu-Yb MOF powder; S2, preparing Cu-Yb MOF powder into Cu-Yb MOF dispersion, adding heat-treated tetrabutyl titanate ethanol solution into the Cu-Yb MOF dispersion, stirring and heating, cooling, washing, and centrifuging to obtain an intermediate; S3. The intermediate is configured into an intermediate dispersion liquid, and the TiO2 / Cu-Yb MOF photocatalyst is obtained by solvent thermal compounding, and the reaction is completed.
2. The method for preparing a TiO2 / Cu-Yb MOF composite photocatalyst according to claim 1, characterized in that: In step S1, the preparation process of the Cu-Yb MOF powder is specifically as follows: dissolving TCPP in an organic solvent, heating to 100-150° C., stirring and heating, adding an organic solvent containing a copper salt, condensing and refluxing at 100-150° C., adding an organic solvent containing an ytterbium salt, continuing to condense and reflux at 110-160° C., cooling to room temperature, washing, centrifuging, and drying to obtain Cu-Yb MOF.
3. The method for preparing a TiO2 / Cu-Yb MOF composite photocatalyst according to claim 2, characterized in that: The mass ratio of the copper salt, ytterbium salt and TCPP is 6 to 10:6 to 10:3; The mass volume ratio of the copper salt to the organic solvent is 7.5 to 12.5 mg / ml; The copper salt is CuCl2; The ytterbium salt is Yb(NO3)3; The organic solvent is DMF.
4. The method for preparing a TiO2 / Cu-Yb MOF composite photocatalyst according to claim 1, characterized in that: In step S2, the mass volume ratio of Cu-Yb MOF to tetrabutyl titanate in the Cu-Yb MOF dispersion is 4:25-100 mg / μL.
5. The method for preparing a TiO2 / Cu-Yb MOF composite photocatalyst according to claim 1, characterized in that: In step S2, the mass volume ratio of Cu-Yb MOF to the dispersion medium in the Cu-Yb MOF dispersion is 0.5-0.8 mg / mL; The volume ratio of tetrabutyl titanate to ethanol in the tetrabutyl titanate ethanol solution is (2.5-10)×10 -3 :
1.
6. The method for preparing a TiO2 / Cu-Yb MOF composite photocatalyst according to claim 1, characterized in that: In step S2, the temperature of the heat treatment of the tetrabutyl titanate ethanol solution is 80-90°C; the temperature of the stirring heating is 80-90°C.
7. The method for preparing a TiO2 / Cu-Yb MOF composite photocatalyst according to claim 1, characterized in that: In step S3, the dispersion medium in the intermediate dispersion liquid includes water and DMF in a volume ratio of 30 to 40:1; The mass volume ratio of the intermediate and the dispersion medium is 2.3-6.9 mg / ml.
8. The method for preparing a TiO2 / Cu-Yb MOF composite photocatalyst according to claim 1, characterized in that: In step S3, the temperature of the solvothermal compounding is 100-150°C.
9. A TiO2 / Cu-Yb MOF composite photocatalyst, prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the TiO2 / Cu-Yb MOF composite photocatalyst as claimed in claim 9 in the field of photocatalysis, wherein the TiO2 / Cu-Yb MOF composite photocatalyst is used as a photocatalyst for hydrolysis to produce hydrogen.
Citation Information
Patent Citations
Ferroferric oxide loaded compound micropowder and application thereof
CN103301460A
Preparation method of conductive polymer imprinted metal ion supported photocatalyst
CN103301886A
Preparation method of heterojunction titanium dioxide / rare-earth doped vanadate composite nanofiber photocatalytic material
CN105457621A
Method for rare earth ions directly exciting triplet state of organic molecules
CN110343525A
Modified TiO2 loaded active porous carbon fiber photocatalytic material and preparation method thereof
CN112473645A